1962
DOI: 10.1001/jama.1962.03050130009003
|View full text |Cite
|
Sign up to set email alerts
|

Pruritic Skin Disease and Summer Air Conditioning

Abstract: (Fig. 1). This effect is produced by the de¬ hydration of the superficial layers of the stratum corneum which then become brittle and chapped or split. This causes an uneven, or rough, surface which can usually be palpated as dry skin or can best be observed under a magnifying lens. The primary lesion just described is the same as that described for dermatitis hiemalis by others.7The patient responds to his symptoms by rubbing or scratching the skin, or both. This leads to the development of erythema and edema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Now termed winter xerosis, the condition is known to be aggravated by the presence of hot, dry air associated with modern central heating. A similar condition has been observed during the summer months in areas with a hot, humid climate where residents spend most of their time in cool, air‐conditioned surroundings [19].…”
Section: What Is Dry Skin?supporting
confidence: 70%
“…Now termed winter xerosis, the condition is known to be aggravated by the presence of hot, dry air associated with modern central heating. A similar condition has been observed during the summer months in areas with a hot, humid climate where residents spend most of their time in cool, air‐conditioned surroundings [19].…”
Section: What Is Dry Skin?supporting
confidence: 70%
“…Eczema typically exhibits a seasonal variation, so ambient temperature is assumed to play an important role in eczema incidence. It was also reported that humidity might be correlated with eczematous eruptions [25,26,27]. However, the associations between environmental temperature, humidity, and eczema incidence have thus far barely been assessed in a direct way.…”
Section: Introductionmentioning
confidence: 99%
“…Several classic case reports and series correlated low humidity with eczematous eruptions (Chernosky, 1962; Gaul and Underwood, 1952; Rycroft and Smith, 1980). In a questionnaire series of 21 dermatologists in 19 countries by Rajka (Rajka, 1986), AD was thought to be related to cold/dry and hot/humid weather.…”
Section: Introductionmentioning
confidence: 99%